Influência da contração de polimerização de resinas compostas no comportamento mecânico de raízes enfraquecidas sob carga estática - Ferreira, Carolina Santos Santana (2015)
Prior cervical reconstruction of weakened teeth roots with endodontic treatment by means of adhesives has been suggested due to the favorable mechanical properties of these materials. However, the polymerization shrinkage of the composite resin should be minimized to ensure adequate adhesion. This study aimed to investigate, through the finite element method, the influence of the use of composite resins of different degrees of polymerization shrinkage in the mechanical behavior of weakened roots of endodontically treated teeth, after intra root reconstruction by adhesive technique. The software Ansys 12.0 (Canonsburg, PA, USA) was used for modeling and processing. Two distinct three-dimensional geometric models were produced, representing a central maxillary incisor with weakened root restored with post / core / ceramic crown and root canal dentine walls reconstrured internally with: light-cured hybrid resin (Filtek Z250-3M ESPE, MN, USA) (Model 1 - anatomic post); lowshrinkage light-cured resin (Surefil SDR-Dentisply, DE, USA) (Model 2A - direct technique); or core resin dual-cured (Clearfil DC Core Automix - Kuraray Medical Inc., Tokyo, Japan) (Model 2B - direct technique). A static load of 100N was applied to the palatal surface of the three models. The distribution of the maximum (S1) and minimum (S3) stress in the three models was analyzed in the isolated root, at reconstruction and cement. S1 and S3 stress at roots and S1 stress at reconstruction and cement demonstrated a similar distribution pattern among the models, with greater magnitude in Models 2A and 2B. Only S3 stress at reconstruction and cement presented a variable distribution pattern among the three models. The magnitude of S1 stress at root indicated possibility of failure in the root dentin with a static load in both models which simulated the polymerization shrinkage, in Models 2A and 2B. The analysis of stress revealed an unfavorable prognosis for the reconstruction of weakened roots by the direct technique, due to the possibility of failure in the adhesive interfaces. When necessary, reconstruction should be performed with hybrid composite resin light-cured by the anatomic post technique.